The Practice of Pancasila Values in the Implementation of Tolerance Among Religious Communities for Students of UIN Mahmud Yunus Batusangkar in Places of Worship in the City of Padang Related to the Letter (QS. Al-Hujurat: 13) and Tafsir Al-Muyassar - Mahmuda; Ridianto (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Pancasila is the foundation of the Indonesian nation that has a function in social life. Pancasila as a tool to unite the nation, the personality of the nation, the outlook on life of the nation, the source of all sources of law and sources of knowledge in Indonesia. Diversity in society is one thing that is very important for social life in the Unitary State of the Republic of Indonesia. As in Pancasila, the third principle which reads